Liquid methane at extreme temperature and pressure: Implications for models of Uranus and Neptune - Richters, D.; Kuehne, Th. D. (Jetp Letters, 2013)
We present large scale electronic structure based molecular dynamics simulations of liquid methane at planetary conditions. In particular, we address the controversy of whether or not the interior of Uranus and Neptune consists of diamond. In our simulations we find no evidence for the formation of diamond, but rather sp2-bonded polymeric carbon. Furthermore, we predict that at high temperature hydrogen may exist in its monoatomic and metallic state. The implications of our finding for the planetary models of Uranus and Neptune are in detail discussed. © 2013 Pleiades Publishing, Ltd.
CRIS-Team Scopus Importer:2023-03-20